Lemmus lemmus - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
31. Norway Brown Lemming Lemmus lemmus French: Lemming de Norvege / German: Berglemming / Spanish: Lemming de Noruega Other common names: Norway Lemming, Norwegian Lemming Taxonomy. Mus lemmus Linnaeus, 1758, Lappmark, Sweden. Lemmus lemmus is closely related to L. sibiricus. The two lemmings easily hybridize under laboratory conditions. Recent phylogeographic analysis showed that L. lemmus did not colonize its current distribution from the south but survived the Last Glacial Maximum in an ice-free Fennoscandian refugium. Monotypic. Distribution. Endemic to Fennoscandia, specifically to the Scandinavian Peninsula (Norway and N & W Sweden), N Finland, and Kola Peninsula (NW Russia); S border fluctuates ¢.200 km, shifting S during cyclic peaks. Descriptive notes. Head-body 112-150 mm, tail 10-18 mm; weight 40-130 g. The Norway Brown Lemming is chunky, with relatively large, broad, and flattened head; small eyes; and short, tufted ears. Tail is slightly shorter than hindfoot, densely haired with long pencil. Palmar and plantar surfaces are densely covered with stiff hairs; pads are vestigial. Females have eight nipples, two pairs of inguinal and two pairs of pectoral. Fur is soft, dense, and long. Pelage is bright black on nose, forehead, shoulders, and proximal back; reddish brown on rest of back and between ears; and buff to yellow on venter and flanks. Black stripe of variable intensity is frequently present along spine. Color varies considerably among individuals, depending on season, age, and sexual status. It can be lighter or rustier, with conspicuous or nearly absent black markings. Three hypotheses were proposed to explain rich coloration that can be aposematic, protective, or a mix of both (i.e. aposematism and crypsis). In any case, Norway Brown Lemmings match the background in certain environments and at certain times (e.g. subalpine sphagnum bogs, birch woods in spring, and subalpine tundra in autumn). Skull is very broad and low, with powerful zygomatic arches that expand abruptly. Rostrum is ...